Pharmaceutical quality evaluation of marketed vildagliptin tablets in Bangladesh based on the United States Pharmacopeia specifications - Islam, Md. Rabiul; Daria, Sohel; Ankhi, Arjina A.; Sultana, Sharmin; Rahman, Md. Ashrafur (Narra Sains Indonesia, 2022)
Continuous monitoring of pharmaceutical products is vital because it matters to human health. Here we aimed to assess the quality parameters of commercially available vildagliptin tablets in Bangladesh. We tested the tablets for the content uniformity, hardness, friability, disintegration, dissolution, and potency. Then, we fitted the dissolution data with kinetic models to investigate the release pattern of the studied brands. Moreover, we applied a mathematical model-independent approach to compare the dissolution profiles of the brands. The interchangeability was determined using difference and similarity factors. Weight variation, friability, and hardness were between 150.35±1.26 to 230.8±1.98 mg, 0 to 0.88%, and 47.3±5.09 to 108.1±1.92 N, respectively. All tablets disintegrated within 0.54±2.85 to 7.69±2.14 min in distilled water. The potency of tablets in 0.1 N HCl and PBS (pH 6.8) were between 97.67±2.58 to 105±0.95% and 99±4.63 to 105±1.65%, respectively. The drug release (%) in 0.1 N HCl and phosphate-buffered saline (PBS) (pH 6.8) after 60 min were between 99.37±1.80 to 111.09±0.64% and 96.59±3.52 to 109.57±0.53%, respectively. All the brands complied with the United States Pharmacopeia (USP) specification for physicochemical properties. Also, we observed the drug release patterns of vildagliptin tablets matched with different kinetic models. We found only one substitutable brand with the standard product regardless of the dissolution medium. In-vitro chemical equivalence is not always consistent with bioequivalence. Therefore, continuous evaluation of marketed products is essential to ensure the desired quality.